2022
DOI: 10.1007/s11030-022-10539-w
|View full text |Cite
|
Sign up to set email alerts
|

Designing a novel SOX9 based multi-epitope vaccine to combat metastatic triple-negative breast cancer using immunoinformatics approach

Abstract: Immunotherapies are a promising treatment option especially for the management of TNBC owing to its higher levels of tumour-associated antigens together with higher mutational load. Of note, the administration of preventive vaccines in the early stage of the cancer holds promise for effective disease management. Therefore, the present study aimed to develop a novel multi-epitope peptide-based vaccination against TNBC employing SOX9, which has recently been recognized as a key regulator of TNBC metastasis. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…This linker also has a rigid helical structure. 20 Whereas the KK, GPGPG, and AAY linkers are hydrophilic amino acids and can prevent domain function disturbances and vaccine folding. The GPGPG linker can stimulate the HTL response and conformation of the bound immunogenicity of HTL, while the AAY linker can increase epitope presentation and eliminate junctional epitopes.…”
Section: Discussionmentioning
confidence: 99%
“…This linker also has a rigid helical structure. 20 Whereas the KK, GPGPG, and AAY linkers are hydrophilic amino acids and can prevent domain function disturbances and vaccine folding. The GPGPG linker can stimulate the HTL response and conformation of the bound immunogenicity of HTL, while the AAY linker can increase epitope presentation and eliminate junctional epitopes.…”
Section: Discussionmentioning
confidence: 99%
“…Sema4A is a signaling protein recently identified as a major regulatory factor in TNBC progression; MZF1 is a transcription factor and a carcinogenic inducer of TNBC metastasis; SOX9 is also considered a key regulatory factor in TNBC metastasis. Using appropriate adjuvants and epitope combinations, these research teams identified and evaluated the potential of antigen peptide-induced immune responses against Sema4A, MZF1, and SOX9, and conducted immune simulation studies and computer cloning on the constructed vaccines, indicating that in the target organisms, the designed chimeric vaccines can elicit robust humoral and cellular immunological responses [29][30][31]. Based on this evidence, these types of vaccines may become a promising therapy for TNBC in the future.…”
Section: Multi-epitope Peptide Vaccinementioning
confidence: 99%
“…Dar et al (2022) implemented a reverse vaccinology approach to determine the immunogenic B, CTL, and HTL epitopes from NT5E, ANPEP, and MME proteins, the putative targets for gallbladder cancer (GBC), and developed a robust peptide-based vaccine against GBC [ 19 ]. Importantly, our team successfully developed an immunoinformatics-based peptide vaccine targeting SOX9, a transcription factor that has been reported as a major regulator of TNBC metastasis [ 20 ]. With these frames of reference, the present study intended to develop a subunit vaccine integrating immunoinformatics methods and simulation studies targeting MZF-1, a recently reported oncogenic inducer, pertaining to the treatment of TNBC patients.…”
Section: Introductionmentioning
confidence: 99%